When Trust is Betrayed: Religious Institutions and White Collar Crime - Fleckenstein, Marilynn P. (Journal of business ethics, 2000)
In 1990, the comptroller of the Catholic Diocese of Buffalo was charged with the embezzlement of eight million dollars of money belonging to the Diocese, He was subsequently convicted and served several years in state prison. Using this case as a starting point, this paper looks at several examples of white-collar crime and religious institutions. Should justice or mercy be the operative virtue in dealing with such criminals?